Clinical significance of distal embolism in intravascular recanalization of the superficial femoral artery - O. S. Osipova; A. A. Gostev; A. A. Karpenko (Кардиоваскулярная терапия и профилактика)
The article discusses different views on distal embolism in endovascular revascularization of lower limb arteries. Attention is drawn to the contribution of the drug coating of the balloon catheter to the development of distal embolization.